Knockdown of ANGPTL2 promotes left ventricular systolic dysfunction by upregulation of NOX4 in mice - Labbé, Pauline; Martel, Cécile; Shi, Yan-Fen; Montezano, Augusto; He, Ying; Gillis, Marc-Antoine; Higgins, Marie-Ève; Villeneuve, Louis; Touyz, Rhian; Tardif, Jean-Claude; Thorin-Trescases, Nathalie; Thorin, Eric (Frontiers in Physiology, 2024)
Background: Angiopoietin-like 2 (ANGPTL2) is a pro-inflammatory and pro-oxidant circulating protein that predicts and promotes chronic inflammatory diseases such as atherosclerosis in humans. Transgenic murine models demonstrated the deleterious role of ANGPTL2 in vascular diseases, while deletion of ANGPTL2 was protective. The nature of its role in cardiac tissues is, however, less clear. Indeed, in adult mice knocked down (KD) for ANGPTL2, we recently reported a mild left ventricular (LV) dysfunction originating from a congenital aortic valve stenosis, demonstrating that ANGPTL2 is essential to cardiac development and function. Hypothesis: Because we originally demonstrated that the KD of ANGPTL2 protected vascular endothelial function via an upregulation of arterial NOX4, promoting the beneficial production of dilatory H2O2, we tested the hypothesis that increased cardiac NOX4 could negatively affect cardiac redox and remodeling and contribute to LV dysfunction observed in adult Angptl2-KD mice. Methods and results: Cardiac expression and activity of NOX4 were higher in KD mice, promoting higher levels of cardiac H2O2 when compared to wild-type (WT) mice. Immunofluorescence showed that ANGPTL2 and NOX4 were co-expressed in cardiac cells from WT mice and both proteins co-immunoprecipitated in HEK293 cells, suggesting that ANGPTL2 and NOX4 physically interact. Pressure overload induced by transverse aortic constriction surgery (TAC) promoted LV systolic dysfunction in WT mice but did not further exacerbate the dysfunction in KD mice. Importantly, the severity of LV systolic dysfunction in KD mice (TAC and control SHAM) correlated with cardiac Nox4 expression. Injection of an adeno-associated virus (AAV9) delivering shRNA targeting cardiac Nox4 expression fully reversed LV systolic dysfunction in KD-SHAM mice, demonstrating the causal role of NOX4 in cardiac dysfunction in KD mice. Targeting cardiac Nox4 expression in KD mice also induced an antioxidant response characterized by increased expression of NRF2/KEAP1 and catalase. Conclusion: Together, these data reveal that the absence of ANGPTL2 induces an upregulation of cardiac NOX4 that contributes to oxidative stress and LV dysfunction. By interacting and repressing cardiac NOX4, ANGPTL2 could play a new beneficial role in the maintenance of cardiac redox homeostasis and function.